2015
DOI: 10.1155/2015/606389
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin-Secreting Neuroendocrine Carcinoma of Larynx with Metastasis to Thyroid

Abstract: Primary neuroendocrine tumors of the larynx are rare, with moderately differentiated neuroendocrine carcinoma (MDNC) being the most frequent histologic type. We report a MDNC in a 57-year-old gentleman with an enlarging right-sided neck mass. Flexible fiberoptic exam revealed a right arytenoid lesion. Histology from excisional biopsy was concerning for medullary thyroid carcinoma (MTC) versus NET of the larynx. Immunohistochemistry was diffusely positive for calcitonin and CEA and focally positive for TTF-1. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…LaBryer et al reported a case of calcitonin secreting neuroendocrine tumor of the larynx with elevated serum calcitonin. In the total thyroidectomy specimen a 4 mm calcitonin positive neuroendocrine carcinoma was identified which was consistent with thyroid metastasis from a primary laryngeal NET . In the three other cases of calcitonin secreting NET of larynx reported by Sweeney et al, Smets et al and Insabato et al, the patients underwent thyroidectomy in all three instances with no evidence of medullary thyroid carcinoma.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…LaBryer et al reported a case of calcitonin secreting neuroendocrine tumor of the larynx with elevated serum calcitonin. In the total thyroidectomy specimen a 4 mm calcitonin positive neuroendocrine carcinoma was identified which was consistent with thyroid metastasis from a primary laryngeal NET . In the three other cases of calcitonin secreting NET of larynx reported by Sweeney et al, Smets et al and Insabato et al, the patients underwent thyroidectomy in all three instances with no evidence of medullary thyroid carcinoma.…”
Section: Discussionsupporting
confidence: 63%
“…Calcitonin‐secreting neuroendocrine tumors outside the thyroid gland are rare. These tumors have been reported in literature as case reports in various organs including lung, pancreas, larynx, bladder and ovary . The frequency of calcitonin secreting neuroendocrine tumors in various organs may be underestimated, as serum calcitonin measurement or immunohistochemical stains for calcitonin is not routinely performed on neuroendocrine tumors of various organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional descriptors pertaining to rare morphologic variants of MTC (e.g., small cell, giant cell) that can be diagnostically challenging would be useful [43,44]. Other diagnostic pitfalls that could be addressed include: (1) Morphological overlap with oncocytic follicular lesions and PDTC [45]; and (2) Morphological and immunohistochemical overlap with other neuroendocrine tumors [46]. In addition, some aspects of the management of MTC have been updated in the 2015 revised ATA guidelines [41].…”
Section: Specific Issues Pertaining To the Different Diagnostic Categmentioning
confidence: 99%
“…There are also sporadic reports of MDNC metastasizing to the lung, liver, and brain (10). There is 1 case report of MDNC metastasizing to the thyroid, but the authors questioned the diagnosis due to the presence of thyroid C-cell hyperplasia (4).…”
Section: Discussionmentioning
confidence: 99%